Fish Diversity and Water Quality of Ayamaru Lake, West Papua - Taufiq Hidayah; Marson Marson; Muhammad Ali; Ni Komang Suryati; Dina Muthmainnah (Sriwijaya Journal of Environment, 2021)
Ayamaru lake is one of the lakes in West Papua categorized as karst lake. It is endowed with fish diversity in various ornamental fish and consumption fish with high economic value. Recently, a number of floating net cages is set up, and before causing serious damage, management for keeping the sustainability of fish resources, especially the endemic species, needs to be proposed.  This paper would contribute information on fish diversity and the water quality of Ayamaru Lake. The study was conducted in March, July, and November 2019 at Ayamaru Lake, Maybrat Regency, West Papua Province. The data were collected by conducting direct survey, interviewing the fishers, and the related institution, as well as searching the previous studies. Fish and water samples were taken from five stations. The results showed that 15 freshwater fishes were identified. The capture fisheries were practiced using the environment-friendly fishing gears. The water quality was still quite useful to support fish life. To reduce the threat to the presence of endemic fish in the lake, it needs to regulate the release of introduced species by the community, and control the escaped fish from the culture area.